Studi Dampak Implementasi Motto Kota Serang dengan Pendekatan Teori Fenomenologi Husserl - Marthalena, Marthalena (Sawala : Jurnal Administrasi Negara, 2017)
Serang City has a symbol in which there is the Motto Serang Madani City. A word that becomes motivation from Serang city in running its government. The motto should be a mutual consensus between the people of Serang City and the city government of Serang. The motto that should have been the way of life of the people of Serang City. Implementation of the Serang City Motto is observed in depth with regard to the visible phenomenology. If the implementation is going well then it will seem the impact in daily life of the people of Serang city associated with the Motto. In his writing, Motto's implementation is reviewed in the areas of hygiene, orderliness, arrangement of street vendors, parking, terminal arrangement and public transportation. The result of this research is to see the various phenomenon that appear in the field can be concluded that the motto of Serang Madani City is not implemented in the middle of life of Serang city because of the low self awareness (self consiusnes) of Serang City to obey the regulations that have been made by the government of Serang City